ISOLATION AND CHARACTERISATION OF COLLAGEN FROM THE WASTE MATERIAL OF TWO IMPORTNT FRESHWATER FISH SPECIES - S. Mahboob; S. Haider; S. Sultana; K. A. Al- Ghanim; F. Al-Misned; H. F. Al-Kahem Al-Balawi; Z. Ahmad (Journal of Animal and Plant Sciences, 2014)
The study was designed to isolate and characterize the collagen from skin, scales and fins of Cyprinus carpio and Hypophthalmichthys molitrix. For this purpose nine fishes of each species of three weight groups were collected and categorized as W1 (250-500 g), W2 (501-750 g) and W3 (751- 1000 g). The maximum skin protein content was recorded as 28.13% and 29.13% in C. carpio and H. molitrix, respectively, from the W3. The scales of the W3 displayed a maximum protein contents as 29.91 and 28.38% for C. carpio and H. molitrix, respectively. The maximum protein contents (19.19% and 21.37% for C. carpio and H. molitrix, respectively) were observed in the W3 group. Protein characterisation using SDS-PAGE revealed the molecular weights (kDa) of the C. carpio skin, scales, and fins ranged from 126 kDa to 220 kDa, 78 kDa to 211 kDa, and 72 kDa to 141 kDa, respectively. The size of the collagen proteins of the H. molitrix skin, scales and fins ranged from 117 kDa to 208 kDa, 81 kDa to 219 kDa, and 72 kDa to 141 kDa, respectively. Glycine was the most abundant amino acid, whereas, Tryptophan was totally absent in all selected tissues. Significant differences were observed for amino acids within the weight groups and between the two fish species.
Keywords: Fish; Proximate composition; weight groups; Amino acids; SDS-PAGE